ANALISIS KESULITAN KETERAMPILAN MENULIS PARAFRASE PUISI KE PROSA SISWA KELAS VI SEKOLAH DASAR - Farida Hikmawati; Irfai Fathurohman; Erik Aditia Ismaya (Universitas Muria Kudus, 2023)
This research is motivated by the low learning outcomes of language skills, especially the skills of writing paraphrasing poetry into elementary school prose. This study aims to obtain the results of the analysis of students' difficulties in writing skills. Paraphrasing poetry to prose for sixth grade elementary school students. The causes are, among others, the teaching methods of teachers who are less diverse, boring, lack of teacher skills that are not suitable for anticipating the difficulties experienced by students, students' lack of understanding of the diction contained in poetry, and lack of writing skills and developing story sentences. The analysis of the difficulties experienced by students in Paraphrasing material converting poetry into prose has never been done, so this affects the score of students who do not meet the KKM set by the school, which is 70. This observation uses a qualitative approach with data collection techniques carried out through observation, interviews and work results. Student. The object of this observation is a grade VI student at SD Negeri 3 Menawan and a document Paraphrasing poetry into prose written by a grade VI student at SD Negeri 3 Menawan. The number of students observed was 23 students. The result of this observation is to find out the students' difficulties in writing paraphrasing poetry to prose. These difficulties include students' difficulties in converting poetry into stories, conveying their thoughts into prose, assembling sentences, and the lack of understanding of the meaning of words in the poetry presented due to the lack of students' vocabulary. Based on the results of the analysis of students' difficulties in paraphrasing poetry, the teacher can determine the steps to teach Indonesian, especially Paraphrasing poetry to prose in elementary schools well.